Researches about suicide in Brazilian graduate program - Maria Dalva Santos Alves; Ângela Maria Alves e Souza; Cynthia Dias Vieira; Talita Maciel Bezerra; Ana Caroline Cabral Cristino (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
The suicide is considered a public health problem and worries governments and health professionals in many countries. We aim to verify the Strict Sense Scientific Production in Brazil, describing the researches achieved in the health area. The descriptive and bibliographical study started in 27th December 2005 in CAPES data bank, via internet, that from the term suicide found 128 dissertations and 50 thesis. The abstracts were read, looking for the studied variables, year and local of defense, knowledge area, instruments and/or strategies of collecting and analysis prepared. The abstracts correspond to 0, 14% of the total registered in CAPES from 1989 to 2003 in the following areas: Literature, History, Sociology, Law, Psychology, Public Health, Nursing, Education, Communication, Medical Sciences and Biological Sciences. The difficulties to become viable this research made us perceive that the programs of Post-Graduation must be attentive to formation of the data sent to CAPES.